Entrepreneurship and structural economic transformation - Thomas Gries; Wim Naudé (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2008)
A stylized fact of economic development is the structural transformation of countries from traditional, mainly agricultural societies to modern economies dominated by manufacturing and services. In this paper we provide an endogenous growth model to illuminate the role of entrepreneurial start-up firms in structural economic transformation. We follow the Lewis-model's distinction between a traditional and modern sector, and underpin this with micro-foundations. We specify mature and startup entrepreneurs and make a distinction between survivalist self-employment activities in the traditional sector, and opportunity-driven entrepreneurship in the modern sector. The model shows how opportunity-driven entrepreneurship can drive structural transformation through innovation, provision of intermediate inputs and services (which permits greater specialization in manufacturing), and by increasing employment and productivity in both the modern and traditional sectors.
Keywords: M13; L26; O10; O14; 330; entrepreneurship; economic development; structural transformation; startups; Entwicklung; Strukturwandel; Neue Wachstumstheorie; Entrepreneurship-Ansatz; Unternehmensgründung; Theorie